2016
DOI: 10.1080/0142159x.2016.1248924
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in medical education

Abstract: Motivation is a concept which has fascinated researchers for many decades. The field of medical education has become interested in motivation recently, having always assumed that medical students must be motivated because of their commitment to highly specific training, leading to a very specific profession. However, motivation is a major determinant of the quality of learning and success, the lack of which may well explain why teachers sometimes observe medical students who are discouraged, have lost interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 20 publications
6
111
0
19
Order By: Relevance
“…The higher these three components of a student’s motivation, the higher his or her motivation. Based upon previous publications, Table 2 describes some relevant strategies in order to reach this goal, for each component of the motivation [9]. …”
Section: Discussionmentioning
confidence: 99%
“…The higher these three components of a student’s motivation, the higher his or her motivation. Based upon previous publications, Table 2 describes some relevant strategies in order to reach this goal, for each component of the motivation [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the higher the level of perceived self-efficacy, the more they choose activities that challenge them and give them the opportunity to develop their skills, and the higher the learning objectives they set [12]. They also better face the difficulties in order to persevere, better regulate their efforts, manage stress and anxiety, and attain a higher level of performance [12]. On the other hand, people tend to engage in tasks in which they feel competent and avoid those in which they don’t [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Le premier renvoie à la difficulté qu'éprouvent les étudiants à mettre en lien le contenu scientifique de leur première année de formation avec le métier auquel ils sont venus se former, conduisant ainsi à une forme de « désenchantement » [2] . Le second résulte du caractère hautement compétitif des études de santé, notamment médicales, qui favorise la motivation à réussir, plutôt que la motivation à apprendre [4] . Certes, ces deux types de motivation, présentent l'un comme l'autre un intérêt, mais celuici est conditionné au fait que la réussite témoigne de la capacité de l'étudiant à mobiliser des stratégies d'apprentissage élaborées sur le plan cognitifconduisant à des apprentissages couramment dénom-més « en profondeur » -, alors même que l'on sait que les modalités d'évaluation, notamment en première année de médecine, n'encouragent pas le recours à de telles stratégies.…”
unclassified
“…La motivation est un construit humain qui ne se voit qu'à travers un certain nombre d'indicateurs permettant d'appréhen-der son niveau chez une personne. Comme tout construit, son appropriation en tant qu'objet d'étude scientifique implique une démarche préalable et obligatoire de conceptualisation, visant à adosser son exploration à l'une des dizaines de théories élaborées dans le cadre des recherches menées dans le domaine de la psychologie et de l'éducation [4] . De l'approche psychanalytique freudienne aux conceptions sociocognitivistes, en passant par les courants humaniste -porté notamment par Maslow -et béhavioriste -marqué en particulier par les travaux de Hull et de Skinner-, la motivation fait l'objet de recherches scientifiques depuis plus d'un siècle [4] .…”
unclassified
See 1 more Smart Citation